2020
DOI: 10.12688/f1000research.27504.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and primary culture of Galleria mellonella hemocytes for infection studies

Abstract: Galleria mellonella larvae are increasingly used to study the mechanisms of virulence of microbial pathogens and to assess the efficacy of antimicrobials.  The G. mellonella model can faithfully reproduce many aspects of microbial disease which are seen in mammals, and therefore allows a reduction in the use of mammals. The model is now being widely used by researchers in universities, research institutes and industry. An attraction of the model is the interaction between pathogen and host. Hemocytes are speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Surprisingly, our results after following the literature [ 14 , 15 , 16 ] showed that almost all of the hemocytes isolated directly from larvae ( Figure 2 A) were nonviable after 24 h of isolation ( Figure 2 B) and completely dead after 6 days (see Figure 2 C). Clearly, these apparently easy protocols described for the cultivation of G. mellonella hemocytes had some limitations, as a similar survival rate was expected during isolation and incubation.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Surprisingly, our results after following the literature [ 14 , 15 , 16 ] showed that almost all of the hemocytes isolated directly from larvae ( Figure 2 A) were nonviable after 24 h of isolation ( Figure 2 B) and completely dead after 6 days (see Figure 2 C). Clearly, these apparently easy protocols described for the cultivation of G. mellonella hemocytes had some limitations, as a similar survival rate was expected during isolation and incubation.…”
Section: Resultssupporting
confidence: 50%
“…The literature contains different protocols for G. mellonella hemocyte isolation and use [ 14 , 15 , 16 ]. As a summary of such protocols, in our laboratory, we obtained hemocytes from larvae of approximately 250 mg.…”
Section: Resultsmentioning
confidence: 99%
“…For TEM assays, hemolymph collected from 10 insects was pooled and centrifuged at 500× g for 10 min at room temperature [ 31 , 32 ] to enrich the preparation with hemocytes without inducing visible cell damage. The supernatant was discarded and the pellet was suspended and fixed in Karnovsky mixture containing 4% formaldehyde and 2% glutaraldehyde in 0.1 M cacodylate buffer for 2 h and processed as previously described [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Trypan blue vital dye is a useful procedure for estimating alterations in membrane permeability associated with cell death in mammals (Louis and Siegel, 2011). The same procedure is often adopted for the evaluation of immune cell viability in different invertebrate species (Rocha et al, 2014;Senior and Titball, 2020). The main drawbacks of this technique are the toxicity of trypan blue, which limits the possibility of using it to few minutes after staining, and the high number of false negatives (e.g., lack of detection of cells already engaged into the apoptotic pathway as they still have intact membranes).…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%